Analisis pengaruh internet marketing terhadap pembentukan word of mouth and brand awareness untuk memunculkan intention to buy - Andriyanto, Richard Darmawan; Haryanto, Jony Oktavian (SBM ITB, 2010)
The purposes of this research are to prove whether internet marketing does give positive influence to the formation of brand awareness and word of mouth, then whether if internet marketing is directly give positive influence to formation of intention to buy. Furthermore, the writer wants to analyze the relationship between brand awareness and word of mouth to create intention to buy. The data was analyzed using structural equation modeling with Amos software. Sample of this research was 130 respondents who are taken by judgment sampling.This research found that internet marketing positively influence brand awareness and word of mouth, but it does not directly give positive influence to intention to buy. Brand awareness also does not give positive influence to word of mouth. Both brand awareness and word of mouth do influence positively to formation of intention to buy.Keywords: Internet Marketing, Brand Awareness, Word of Mouth, Intention to Buy